Model of Steam Consumption in Central Heat Transfer Network - Šípal, J. (Elektronika ir Elektrotechnika, 2007)
A semi-empiric mathematical model capable to predict future consumption of heat energy in a central heat transfer network is presented. This prediction is important for producers, because it can help to save operational costs of a heat station and it can improve the efficiency of electrical energy production. This model is applied on real heat stations and a good match with real data is obtained. Ill. 7, bibl. 4 (in English; summaries in English, Russian and Lithuanian).